2014
DOI: 10.1149/06001.1153ecst
|View full text |Cite
|
Sign up to set email alerts
|

(Invited) Design and Simulation of a Novel Shock Accelerometer Based on Giant Piezoresistance Effect

Abstract: The design of a novel eight-beam uniaxial shock accelerometer is presented. This new multi-beam structure has an advantage of high anti-disturbance capability. The designed measurement rang of the sensor is 150,000g and the sensitivity is 23.4µV/g, which is about 20 times higher than conventional sensors of same measurement rang due to the exploiting of the giant piezoresistance effect in silicon nanowires. This achievement opens up new developments in the area of shock experiments where the high overload capa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…One notes that the sensitivity of the proposed SiNW piezoresistive pressure sensor in this paper can be increased to more than four times as compared to that of SiNW pizoresisitve pressure sensor without the giant piezoresistive effect [ 12 ], which can be attributed to the obvious enhanced surface effect and corresponding giant piezoresistive effect of SiNW [ 31 , 32 , 33 , 34 ]. Recently, Sun et al measured the piezoresistive coefficients of a series of SiNWs with different length and width [ 40 ]. It is also confirmed that there are giant piezoresistive properties in the silicon nanofilms, and their piezoresistive coefficients can increase even up to 1203 × 10 −11 Pa −1 , which is much higher by one order of magnitude than that of bulk silicon.…”
Section: Experimental Section and Discussionmentioning
confidence: 99%
“…One notes that the sensitivity of the proposed SiNW piezoresistive pressure sensor in this paper can be increased to more than four times as compared to that of SiNW pizoresisitve pressure sensor without the giant piezoresistive effect [ 12 ], which can be attributed to the obvious enhanced surface effect and corresponding giant piezoresistive effect of SiNW [ 31 , 32 , 33 , 34 ]. Recently, Sun et al measured the piezoresistive coefficients of a series of SiNWs with different length and width [ 40 ]. It is also confirmed that there are giant piezoresistive properties in the silicon nanofilms, and their piezoresistive coefficients can increase even up to 1203 × 10 −11 Pa −1 , which is much higher by one order of magnitude than that of bulk silicon.…”
Section: Experimental Section and Discussionmentioning
confidence: 99%